Círculo de Bakhtin: uma análise dialógica de discurso - Paula, Luciane de [UNESP] (Faculdade de Letras da UFMG, 2013)
This article proposes a reflection on a place for epistemological studies about the Bakhtin Circle, as well as it also reflects on the perspectives of Brazilian approaches to that. It also sheds light to the issues concerning the production, the circulation and the reception of works of the Russian Circle in order to understand why, in Brazil, we can speak of Dialogic Discourse Analysis (DDA), affiliating the so-called dialogical philosophy of language to an analytical theory, grounded in the relation between linguistics and cross-linguistics. In order to do that, this paper focuses on the notions of dialogue, ideological sign, subject and exotopia. The hypothesis put forward is that, unlike other Analyzes of Discourses, the theoretical-analytical method of the Circle is dialogical. This is the peculiarity of its proposal.

Este artigo propõe pensar um lugar epistemológico para os estudos do Círculo de Bakhtin e reflete sobre as perspectivas de abordagens brasileiras. Ele reflete, de maneira panorâmica, acerca das questões de produção, circulação e recepção das obras do Círculo russo, a fim de compreender porque, no Brasil, é possível se falar em Análise Dialógica de Discurso (ADD), filiando a denominada filosofia dialógica da linguagem como uma teoria analítica calcada no trânsito entre a linguística e a translinguística. Para isso, centra-se, especificamente, em noções como diálogo, signo ideológico, sujeito e exotopia. A hipótese defendida é a de que, diferentemente de outras Análises de Discursos, o método teórico-analítico do Círculo é o dialógico. Essa é a peculiaridade de sua proposta.
Bakhtin Circle: a Dialogical Analysis of Discourse
Keywords: Discourse; Bakhtin Circle; Brazil; Discurso; Círculo de Bakhtin; Brasil